PHYTOCHEMICALS, IN VITRO ANTIOXIDANT ACTIVITY AND PROXIMATE COMPOSITION OF SEEDS OF ENTADA PHASEOLOIDES LINN. MERRILL. - CHANDANA CHOUDHURY BARUA; MOUSUMI HAZORIKA; JYOTI MISRI; SUPARNA SEN; MONDIRA BORA; BIBEKA NANDA SAIKIA; MINESWAR HAZARIKA (International Journal of Pharma and Bio Sciences, 2015)
In the present study, the chemical composition and in vitro antioxidant activity of methanol extract of seeds of Entada phaseoloides were analyzed by various in vitro antioxidant models viz. DPPH radical FRAP and ABTS assay along with the evaluation of IC50 value. Screening of the phytochemical constituents and high performance liquid chromatography (HPLC) analysis of the methanol extract of Entada phaseoloides were performed for identification of some of the functional compounds present in the seeds. The methanol extract of Entada phaseoloides exhibited a significant ascending trend of percentage inhibition with maximum activity at 60μg/ml and 80μg/ml concentration for all the models of free radical scavenging activity. The results showed high amount of phenolic and flavonoids, confirmed by HPLC analysis, and thus it might be an alternative to the synthetic antioxidants available in the market. The chemical composition analysis revealed a high quantity of protein, carbohydrate, fat and minerals. The results demonstrated that the seeds of Entada phaseoloides exhibits an excellent antioxidant activity with high level of nutrients and thus presents a great potential as a source of highly nutritious potent natural antioxidants.